(untitled) (Research, Society and Development, 2021)
Onions are an economically important crop for Brazil and its production has been growing in several regions of the country. The São Francisco Valley region is considered of great agricultural potential, attracting several investments in agriculture. The greater post-harvest conservation is important for the occasion of the commercialization of onions, which presents large price variations in short periods of time. The producer, depending on the knowledge of mass losses, will be able to achieve better price quotes and increase their profits, due to the volatility of the ceboleiro Market. This study aimed to evaluate physical-chemical characteristics and postharvest losses of the cultivar "Botucatu Population" produced at the Bebedouro Experimental Station, belonging to EMBRAPA Semiarid, Petrolina (PE). The statistical design used was completely randomized with 6 treatments and 6 replicates. The experiments were carried out at the Agricultural Products Storage Laboratory (LAPA) of the Agricultural and Environmental Engineering Collegiate of UNIVASF in Juazeiro (BA). The bulbs were stored under ambient conditions of 27ºC ± 2ºC and relative humidity of 75% ± 5% for 75 days. Where he observed that bulbs stored at room temperature have significant mass losses in relation to storage time mainly from 45 days.